A holistic approach for performance evaluation using quantitative and qualitative data: A food industry case study. (15th September 2017) - Duman, Gazi Murat; Tozanli, Ozden; Kongar, Elif; Gupta, Surendra M.
Highlights: A hybrid MCDM model with Fuzzy AHP, DEA (Cross-Efficiency) and TOPSIS is presented. A real life case study involving twenty franchised food stores is provided. Qualitative and quantitative performance measures are introduced. Abstract: Sustainability of business is often reliant on the efficiency of its internal and external operations as well as on overall customer satisfaction. Evaluating overall operational performance via utilizing both qualitative and quantitative information is an essential first step towards a sustainable and reliable business environment. With this motivation, this study proposes a hybrid approach combining Fuzzy AHP, DEA and TOPSIS methodologies for retail performance evaluation. A food industry case study is considered to illustrate its implementation.